PROBLEM WITH TWO-POINTS CONDITIONS FOR SYSTEM PARABOLIC EQUATIONS OF SECOND ORDER ON TIME - Тимків, Іван Романович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
The correctness of the problem with two-points conditions on time variable and Dirichlet type conditions on spatial coordinate for the system parabolic equations of second order on time. The conditions of existence and uniqueness solution of the problem are established. The metrical theorem on evalution from below of small denominators of the problem are proved.